Perbandingan Tepung Ketan dan Labu Siam (Sechium Edule) Terhadap Karakteristik Dodol - I Gede Arisudana; Anak Agung Made Semariyani; I Putu Candra; Luh Suriati (GEMA AGRO, 2018)
This study aims to determine the effect of the ratio of glutinous rice flour and the squash to the resulting dodol characteristics, and to obtain the appropriate ratio of glutinous flour and pistachio to produce dodol with good characteristics and acceptable to consumers. This study used Randomized Block Design (RBD) with 6 (six) comparative treatments namely: T0 (100% glutinous flour: 0% squash); T1 (80% glutinous flour: 20% squash): T2 (70% glutinous flour: 30% squash); T3 (60% glutinous flour: 40% squash); T4 (50% glutinous flour: 50% squash and T5 (40% glutinous flour and 60% squash) Each treatment was repeated 3 times to obtain 18 units of experiments. Based on the results, it can be concluded that the ratio of glutinous flour and gourd flakes have significant effect on water content, ash content, crude fiber content, pH, total sugar, texture, aroma, flavor and overall acceptance of dodol squash. The ratio of 70% starch flour and 30% pumpkin yields a good dodol of cauliflower and not significantly different from the control (100% glutinous flour: 0% squash). Characteristic dodol pumpkin with a ratio of 70% glutinous flour: 30% squash is as follows: water content 19.774%, ash 0.763%, crude fiber 0.925 %, pH 6.270, total sugar 14.660 brix, 4.286 (chewy, elastic, non-breakable) texture taste, 3.000 aroma (somewhat typical dodol squash), 4.286 (sweet legit) flavor, overall acceptance 5.714 (likes) and all these characteristics meet per the requirement of SNI dodol (SNI 01-2986-1992).